Bisnis Toko Online - Decky Hendarsyah (Iqtishaduna: Jurnal Ilmiah Ekonomi Kita)
Indonesian is a large country where the population is included in one of the largest countries in the utilization of information and communication technology. The Indonesian government through the Ministry of Communications and Information committed to accelerating the development of communications infrastructure and the Internet to remote areas throughout Indonesia. This is a great opportunity for the Indonesian people to use the Internet so it can be extended to all areas of life from business, education, health and others as a form of advances in technology and information. Communities can use the Internet ranging from information in the newspaper online, make friends online, online consultation, online business and so on. In the business world, itself has been a shift from traditional business (offline) to the online business. Online business is a huge range and shape, but in this paper, focus discusses the online store. Discussion ranging from the introduction of an online business, a reason to do business online, nothing any forms of online business, how to prepare to start a business online store, how the strategy of customer service and how to shop online store business management and how to store promotion strategy online.